Results of simulation of grouses’ accounting - V. M. Kozlov; S. V. Khalturin (Аграрная наука Евро-Северо-Востока, 2017)
With the help of computer simulation it was studied the peculiarities of extrapolation, identify the error and distortion data based on the number of grouses on the transect (routes), determined the needed length of the routes. The importance of the study lies in the fact that it is impossible to establish the accuracy of counts of birds in transects by another method since in nature it is impossible to determine the true number of birds in a particular area; but this technique is widely used in hunting and scientific research. Records are simulated in the territory of 60 000 hectares. The length of the routes here was 200 km; the bandwidth accounting is 100 m. Т1ю point of birds imitating on-site moved randomly after each calculation cycle of calculation of population density and extrapolation of data. Tenfold passes of routes in each of the three variants of points distribution in the square are simulated that corresponds to different quality of living environment of birds in nature. The limitations of the technique, which requires more work to get a reasonable accuracy, are shown. Accuracy of the registration necessary for practice is achieved when the length of the routes is of 3-5 km per 1000 hectares of land and depends on the density of bird population. Multiple passages of routes are needed. At high density, the smaller length of routes is allowable. It is expedient to lay routes over the entire area of land but not only in the peculiar species habitats; and the result must be extrapolated to entire area. This increases the accuracy of the account and allows taking into account the grouse, capercaillie and grouse simultaneously although their habitats are not always the same. The route length of a few tens of kilometers practiced in the farms does not allow to judge about even the trends of changes in the number because of larger errors. These conclusions are applicable to the accounting of grouse during the winter route accounting.